PENGARUH FAKTOR –FAKTOR KARAKTERISTIK BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATEN ASAHAN - Ery Dermawan; Ulfah Nuri; Rusdi Sibagariang; Edison Rambe; Arfan Sutono (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2021)
This research discusses about the influences of innovation, detail attention and output orientation on employees’ performance at Community and Village Empowerment of Asahan Regency. The aim of this research is to analyse influences of innovation, detail attention and output orientation both partially and simultaneously on employees’ performance at the office. This is a quantitative research with total sampling technique. Sample is 45 employees. Results show that each independent variable; innovation, detail attention and output orientation, partially influences employees’ performance positively and significantly. Innovation has tcount  value 3,795 and level of significance 0.000, detail attention has 4,188 and 0.010, and output orientation has 5,435 and 0.000. Simultaneously, innovation, detail attention and output orientation have significant and positive influences on employees’ performance at Community and Village Empowerment of Asahan Regency with Fcount value 45,204 and level of significance 0.000.